(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Dialectisms are related to the delimited lexical layer of a language and are distinguished from other lexical units by belonging to a particular area and intelligibility for that area. These units, in the language of Motion Pictures, not only represent the region, character, attitude to People, national colorit, but also determine the level of Motion Pictures. The use of dialecticisms in the language of Motion Pictures according to an orthological criterion ensures that it does not compromise the level of Motion Pictures.